(untitled) (Reflection and Critique Law Magazine, 2019)
The article refers to the theme related to the stabilization of the antecedent advance protection in the public civil action. The evolution of the Brazilian collective process microsystem and the provisional tutelage provided for in CPC / 2015 are analyzed. The specific problem to be addressed is related to the relevance of the stabilization of early protection required in the public civil action.